Sociolinguistic Insights into Youth Language Phenomena: Patterns and Influences in South Jakarta through the Lens of #BeritaAkhirPekan Podcast - Mac Aditiawarman; Dewirahmadanirwati Dewirahmadanirwati; Ridha Hasnul Ulya (STAI Hubbulwathan Duri, 2025)
Language use among urban youth, particularly in South Jakarta, has become an intriguing topic in sociolinguistic studies. This study analyzes the phenomena of code-mixing, code-switching, and language interference in the digital platform of the #BeritaAkhirPekan podcast. Using a qualitative approach and content analysis method, data were collected through podcast selection, verbatim transcription of conversations, and categorization based on the observed linguistic phenomena. The findings reveal that code-mixing is frequently employed to reflect modernity, global exposure, and social status, whereas code-switching is strategically used to clarify messages and create a professional and global impression. Language interference occurs at the morphological and phonological levels through the adaptation of terms. These findings have significant implications for language education, particularly in teaching strategies for bilingual or multilingual students. The patterns of code-mixing and code-switching can serve as authentic resources in language learning to enhance linguistic awareness and effective communication. Furthermore, this study’s findings can inspire curriculum development that is more adaptive to the modern linguistic dynamics of urban environments. The integration of digital platforms such as podcasts in language learning can also enrich digital literacy, critical thinking, and cultural awareness. In teacher training, it is crucial for educators to recognize and incorporate students' bilingual practices to create an inclusive learning environment. From a language policy perspective, this study recommends support for bilingualism in schools and adjustments to assessment standards to better reflect real-world linguistic practices.